Health‐related quality of life after restrictive versus liberal RBC transfusion for cardiac surgery: Sub‐study from a randomized clinical trial. Issue 10 (6th September 2022) - Hu, Raymond T.; Royse, Alistair G.; Royse, Colin; Scott, David A.; Bowyer, Andrea; Boggett, Stuart; Summers, Peter; Mazer, Cyril David
Abstract: Background: Transfusion Requirements in Cardiac Surgery III (TRICS III), a multi‐center randomized controlled trial, demonstrated clinical non‐inferiority for restrictive versus liberal RBC transfusion for patients undergoing cardiac surgery. However, it is uncertain if transfusion strategy affects long‐term health‐related quality of life (HRQOL). Study Design and Methods: In this planned sub‐study of Australian patients in TRICS III, we sought to determine the non‐inferiority of restrictive versus liberal transfusion strategy on long‐term HRQOL and to describe clinical outcomes 24 months postoperatively. The restrictive strategy involved transfusing RBCs when hemoglobin was <7.5 g/dl; the transfusion triggers in the liberal group were: <9.5 g/L intraoperatively, <9.5 g/L in intensive care, or <8.5 g/dl on the ward. HRQOL assessments were performed using the 36‐item short form survey version 2 (SF‐36v2). Primary outcome was non‐inferiority of summary measures of SF‐36v2 at 12 months, (non‐inferiority margin: −0.25 effect size; restrictive minus liberal scores). Secondary outcomes included non‐inferiority of HRQOL at 18 and 24 months. Results: Six hundred seventeen Australian patients received allocated randomization; HRQOL data were available for 208/311 in restrictive and 217/306 in liberal group. After multiple imputation, non‐inferiority of restrictive transfusion at 12 months was not demonstrated for HRQOL, and the estimates were directionally in favor of liberal transfusion. Non‐inferiority also could not be concluded at 18 and 24 months. Sensitivity analyses supported these results. There were no differences in quality‐adjusted life years or composite clinical outcomes up to 24 months after surgery. Discussion: The non‐inferiority of a restrictive compared to a liberal transfusion strategy was not established for long‐term HRQOL in this dataset. Abstract : See editorial on page 1929–1932,  in this issue